Engineering-geological conditions of landslides above the settlement of Koroška Bela (NW Slovenia) - Tina Peternel; Jernej Jež; Blaž Milanič; Anže Markelj; Mateja Jemec Auflič (Geologija, 2018)
This paper focuses on the studying of landslides in the hinterland area of the Koroška Bela settlement, NW Slovenia. Research has shown that these landslides have the potential to mobilize the material into a debris flw. The area of interest is located on the Karavanke mountain ridge, above the settlement of Koroška Bela, which lies on the outskirts of the town of Jesenice. In order to recognize and understand the kinematics of landslides and their triggering mechanisms, a multidisciplinary approach using engineering-geological and geotechnical investigations was applied. Thus, landslide source areas were determined based on engineering-geological mapping. Furthermore, landslide boundaries, types of landslides and sediments that are involved in processes of sliding were mapped in detail. Geotechnical monitoring is benefiial in evaluating rates of movement and failures in the ground under real conditions in the fild. Current investigations as well as historical evidence and previous research prove that the hinterland of Koroška Bela is prone to various types of landslides that together form a source area that has the potential to mobilize into larger debris flw.